Antimicrobial Stewardship: Leveraging the "Butterfly Effect" of Hand Hygiene - Adrian John Brink; Guy Antony Richards (MDPI AG, 2022)
It is vital that there are coordinated, collaborative efforts to address the threat of antimicrobial resistance (AMR) and to prevent and control the spread of hospital-onset infections, particularly those due to multidrug-resistant (MDR) pathogens. The butterfly effect is a concept in which metaphorically speaking, small, seemingly trivial events ultimately cascade into something of far greater consequence, more specifically by having a non-linear impact on very complex systems. In this regard, antimicrobial stewardship programs (ASP), when implemented alongside infection prevention control (IPC) interventions in hospitals, particularly hand hygiene (HH), are significantly more effective in reducing the development and spread of AMR bacteria than implementation of ASP alone. In this perspective, we briefly review the evidence for the combined effect, and call for closer collaboration between institutional IPC and ASP leadership, and for well-functioning IPC programs to ensure the effectiveness of ASP.